The residue of the western missionary in the southern Cameroons the Christian village : a sad tale of strife and dissension - Awoh, Peter Acho. (Mankon, Bamenda : Langaa Research & Publishing CIG ; Oxford : Distributed in and outside N. America by African Books Collective, 2012)
This book is the study of Christian enclaves in the Southern Cameroons of the colonial era.
Introduction -- Shishong Christian village -- The Christian village of Njinikom -- The Baseng Christian village.
Includes bibliographical references (p. 397-409).
Description based on print version record.
Keywords: Missions -- Cameroon -- History; Cameroon -- Church history; RELIGION / Christian Ministry / Missions; Electronic books